2011
DOI: 10.1007/s12369-010-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliable People Detection Using Range and Intensity Data from Multiple Layers of Laser Range Finders on a Mobile Robot

Abstract: Reliable people detection is an important task in several areas like security, intelligent environments and human robot interaction. People detection does not depend only upon separation of static environment objects from those showing motion (hopefully humans), a reliable system should be able to detect static people even in cluttered environments.This work presents a reliable approach for people detection and position estimation using multiple layers of Laser Range Finders (LRF) on a mobile robot. Each layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Specific arrangements with WiFi signals can be also used to detect bi-directional motion [30,31]. Very promising is the expansion from a single point measurement to a scanning range [17,18], which also includes an increased effort in the post processing. Nevertheless, the inclusion of a further sensor type will be considered as part of the future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific arrangements with WiFi signals can be also used to detect bi-directional motion [30,31]. Very promising is the expansion from a single point measurement to a scanning range [17,18], which also includes an increased effort in the post processing. Nevertheless, the inclusion of a further sensor type will be considered as part of the future work.…”
Section: Discussionmentioning
confidence: 99%
“…Far better results could be reached with a time of flight (ToF) distance sensor, which is typically used as a scanning device [12][13][14][15] rang finder [16][17][18] and gesture detection sensor [19]. The used VL53L0X module is capable of capturing distances up to a maximum range of 2 m with a very high accuracy.…”
Section: Combination Of the Sensorsmentioning
confidence: 99%
“…To distinguish them from static objects, geometric and statistical features [20], theoretical shape models [21], laser reflection intensity [22] or a threshold [16,17] can be used. The clustering threshold can be chosen empirically as a constant [17] or time-variant value [16].…”
Section: Open Accessmentioning
confidence: 99%
“…This threshold is generally a user-defined value (Weinrich et al, 2014;Mozos et al, 2010;Spinello and Siegwart, 2008;Arras et al, 2007) or determined by a geometric rule (Li. et al, 2018;Borges and Aldon, 2004;Carballo et al, 2011;Kim et al, 2016). * Corresponding author Then, the features of each segment are calculated and used to classify the segment into leg and non-leg.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Spinello and Siegwart (2008) presented multidimensional features and shape descriptors that describe geometrical and statistical properties of the segment to detect legs in 2D range data and obtained desirable detection result. Carballo et al (2011) studied laser intensity and textiles, introduced a group of new intensity-based detection features, and proposed a method for segment separation based on laser intensity. They demonstrated that their proposed intensity-based features improved the detection result.…”
Section: Introductionmentioning
confidence: 99%